2011
DOI: 10.1016/j.leukres.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic repolarization of T lymphocytes from chronic lymphocytic leukemia patients using 5-aza-2′-deoxycytidine

Abstract: T cell immune dysfunction has an important role in the profound immunosupression that characterizes chronic lymphocytic leukemia (CLL). Improper polarization of T cells has been proposed as one of the mechanism involved. Mounting data implicates chromatin regulation, namely promoter methylation, in the plasticity of naïve human T cells. Recent in vitro evidence indicates that this plasticity may be phenotypically altered by using methylation inhibitors which are approved for clinical use in certain types of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, Schmiedel found that although initially impaired, IFN-γ production was recovered and even increased as compared to controls when NK cells were treated for 4 days with 5-aza under IL-2 stimulation [ 33 ] thereby supporting our results that proliferating cells with active incorporation of 5-aza acquire a heightened functionality. A recent study also demonstrated that decitabine treatment can depolarize Th2 cells to effectively secrete IFN-γ, signal via T-bet, and achieve demethylation of critical Th1 specific promoters [ 49 ]. The net effect of 5-aza on NK cell anti-tumor responses was recently investigated in B cell precursor acute lymphoblastic leukemia (BCP-ALL) bearing humanized mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, Schmiedel found that although initially impaired, IFN-γ production was recovered and even increased as compared to controls when NK cells were treated for 4 days with 5-aza under IL-2 stimulation [ 33 ] thereby supporting our results that proliferating cells with active incorporation of 5-aza acquire a heightened functionality. A recent study also demonstrated that decitabine treatment can depolarize Th2 cells to effectively secrete IFN-γ, signal via T-bet, and achieve demethylation of critical Th1 specific promoters [ 49 ]. The net effect of 5-aza on NK cell anti-tumor responses was recently investigated in B cell precursor acute lymphoblastic leukemia (BCP-ALL) bearing humanized mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that not only can boswellic acid be used to treat asthma but also exert antitumor effects. Furthermore, it was effective in treating rheumatism, rheumatoid arthritis, colitis, and inflammatory reactions (Yao et al, 2011;Dubovsky et al, 2011;Souza et al, 2012;Li et al, 2013;Menet et al, 2013;Chakilam et al, 2013). Due to the relationship between asthma and inflammation, we found it valuable to investigate the expression of transcription factors associated with the inflammatory reaction to clarify the mechanism of action of boswellic acid.…”
Section: Discussionmentioning
confidence: 99%
“…While the presumed mechanism of action of these compounds was a direct antitumor effect, they can simultaneously modify antitumor immunity. Thus, they may not only act at the level of tumor cells, by modulating antigen expression and the machinery responsible for their presentation and recognition by T-cells [16,17], but they may also directly act on the immune system, activating effector cells [18,19] and inhibiting immunosuppressive mechanisms [20,21]. Accordingly, some of these compounds increase the efficacy of checkpoint inhibiting antibodies in different murine tumor models [22,23].…”
Section: Introductionmentioning
confidence: 99%